Strategic Returns from CSR : A critical review of Warby Parker’s CSR initiative - Mamatov, Mirjamol; Ryška, Tomáš, 1976-; Sieber, Patrik, 1977-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
This thesis investigates how Corporate Social Responsibility (CSR) initiatives can be strategically implemented to enhance a strategic outcome - a company's brand image. Through a qualitative case study of Warby Parker, the research analyses the alignment of CSR with core business objectives, stakeholder engagement in CSR development, and communication of CSR efforts. Drawing upon stakeholder theory, the CSR Brand Positioning Grid, and the Triple Ba Bottom Line approach, the study provides insights into Warby Parker's successful integration of CSR into its business strategy. The findings highlight the importance of authentic leadership commitment, employee involvement, and strategic partnerships in driving effective CSR outcomes. By critically examining Warby Parker's CSR approach, the thesis offers valuable lessons and best practices for companies seeking to develop or enhance their CSR strategies, contributing to the literature on strategic CSR and its potential to drive business performance and social impact.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses